Pearls and Pitfalls of Oblique Lateral Interbody Fusion: A Comprehensive Narrative Review - Kim, Hyoungmin; Chang, Bong-Soon; Chang, Sam Yeol (Neurospine, 2022)
Lumbar degenerative disease is a common problem in an aging society. Oblique lateral interbody fusion (OLIF) is a minimally invasive surgical (MIS) technique that utilizes a retroperitoneal antepsoas corridor to treat lumbar degenerative disease. OLIF has theoretical advantages over other lumbar fusion techniques, such as a lower risk of lumbar plexus injury than direct lateral interbody fusion (DLIF). Previous studies have reported favorable clinical and radiological outcomes of OLIF in various lumbar degenerative diseases. The use of OLIF is increasing, and evidence on OLIF is growing in the literature. The indications for OLIF are also expanding with the help of recent technical developments, including stereotactic navigation systems and robotics. In this review, we present current evidence on OLIF for the treatment of lumbar degenerative disease, focusing on the expansion of surgical indications and recent advancements in the OLIF procedure.